Simulating the effect of environmental flow duration on seedling emergence from riparian seed banks of the Upper Hunter River, New South Wales. (26th October 2018) - Stone, Luke; Fryirs, Kirstie; Leishman, Michelle
Abstract: Passive riparian revegetation techniques are important tools in river rehabilitation. However, the utility of the sediment seed bank as a passive riparian regeneration option is poorly understood. After modelling a range of flows for field‐surveyed cross sections, a glasshouse seedling emergence experiment was undertaken to compare the effects of simulated flow duration on seedling emergence of desirable riparian species that occur on benches of the gravel‐bedded Hunter River near Muswellbrook, New South Wales. The duration of inundation did have an effect (although not always significant) on seed germination for most species. The most successful simulated flood conditions differed among species, with the control treatment (no inundation) resulting in the most germination for only two of the 10 species examined. These findings suggest that although environmental flows for the sole purpose of stimulating the riparian seed bank in order to facilitate regeneration of desirable riparian species would be largely ineffective and complicated by differing inundation responses among species, seed bank stimulation using environmental flows could be a value‐added benefit from flows allocated for other purposes. As such, consideration of flow duration is worthy of inclusion in environmental flow allocation planning.